ANALYZE LIQUIDITY AND PROFITABILITY IN ORGANIZATION - Ashbin Mathew; M. SINDHUJA (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In the present context, liquidity management and profitability of a company are important for the financial management choice in particular. Only companies that can maintain a balance between profitability and liquidity position of the company can achieve the most acknowledged fiscal performance. The major aim of this research is to understand their significance. Researchers are interested in the study of car firms in this respect. Managers are known to improve profits and maintain liquidity by focusing on several corporate ratios, such as current, liquidity, etc. It may also stress that the cost of the items sold is maintained and the many sectors of operations analysed in order to boost the country’s financial condition. The conclusion reveals that the present ratio and liquid ratio are positive with the profitability of Kerala’s manufacturing enterprises while the cash conversion period is negative. In all of the situations, however, the link was statistically insignificant, demonstrating a minimal degree of liquidity effects on productivity. Therefore, a more realistic credit strategy that would generate less cash conversion period (CCP) would enhance the overall liquidity situation such that it would have a beneficial influence on the company’s profitability.